Exploring the Mayangna Culture of Nicaragua through the SWOT (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
An exploration in one of the indigenous nations of Central America using the SWOT technique that is usually used in the business area. The authors have visited the Mayangna population and have read about them as part of the empathy process. They are doing so with the hope of eventually creating a culturally sensitive program to help the Mayangna leadership achieve the goals they set for their nation and their communities. This is a special region of a special country and far from the typical tourist destinations. Through work with the University of the Autonomous Regions of the Nicaraguan Caribbean Coast (URACCAN), presentations and access to the Sumu - Mayangna Nation were obtained. The document is an exploration of what has been learned up to the date of October 2017.
Keywords: SWOT, Mayangna, Culture, Ethnography, Design thinking